PERAN DEWAN KOMISARIS DALAM MEMODERASI PROFITABILITAS PADA HARGA SAHAM INDUSTRI CONSUMER GOODS INDONESIA - Annisa Shaffana Amalia; Anita Evrilianingsih (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2023)
This study seeks to empirically evaluate the influence of Return on Assets (ROA) and Net Profit Margin (NPM) on stock prices that are moderated by the size of the board of commissioners (BoC). An archival study using the Moderated Regression Analysis (MRA) technique was conducted on consumer goods businesses that are listed on the Indonesia Stock Exchange (IDX) for the years 2015 through 2019. The purposive sampling method was used to compile a sample of 61 firms. The study's findings indicate that ROA and NPM positively affect stock prices. While the influence of NPM on company stock prices cannot be changed, the size of the BoC can enhance the impact of ROA on stock prices. The findings of this research may be useful to investors, corporate management, and other stakeholders when making decisions in the future.